IMPLIKASI YURIDIS PERJANJIAN PERBATASAN MARITIM AUSTRALIA DAN TIMOR LESTE TAHUN 2018 TERHADAP BATAS WILAYAH LAUT INDONESIA DAN AUSTRALIA TAHUN 1972 - Utami, Retno Tri; Deliana, Evi; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Indonesia as a sovereign country cannot escape from international legal joints, even to define and establish something that is a symbol of the sovereignty of the country, territory or Sea also known as as the sea area is the closest zone from the coast is entirely subject to the sovereignty of coastal States, the basis of enactment of sovereignty as the supreme power of the State is limited by the territory of the country, so that the State has the power the highest within the limits of its territory.This research uses the normative legal research typology, which more specifically discusses the principles of law. In this study the author uses descriptive research properties, because the author describes the fact that examined by the researchers of borderline related maritime region Sea Treaty indonesia Australia and East Timor against the territorial boundaries of the sea Indonesia And Australia of the year 1972, the results of the research conducted was the author of, first, what happened in Indonesia and Australia Agreement does not reflect a country's sovereignty have equality. on its implementation should Australia respects the Treaty with indonesia accompanied by consideration of the provisions of article 51 unclos. Second, what happened in Australia-East Timor-Indonesia does not reflect a country's sovereignty have equality. The territorial area for coastal States is the subject of a very important restriction that the absence of rights for other States. When reviewing the context of the implementation of this agreement, then East Timor, on the implementation of East Timor-Australia should respect the content of the Covenant of Indonesia and Australia of the year 1972.Keyword : Agreement-Sea Borders-Sovereignty